The Impact of Renewable Energy Consumption and Economic Growth on CO2 Emissions: New Evidence using Panel ARDL Study of Selected Countries - Shaari, Mohd Shahidan; Abidin, Noorazeela Zainol; Karim, Zulkefly Abdul (International Journal of Energy Economics and Policy, 2020)
Most countries consume more non-renewable energy to generate economic activities. Hence, economic growth plays an important role in contributing to higher CO2 emissions. Therefore, this type of energy has been reduced and replaced by renewable energy. Renewable energy is said not to be detrimental to the environment. Therefore, it is imperative to examine the effects of renewable energy consumption and economic growth on CO2 emissions in selected countries by per capita income. The panel ARDL method was employed and the results show that in the long run, overall renewable energy consumption can reduce CO2 emissions. However, overall economic growth and overall population growth can result in higher CO2 emissions in the long run. In the short run, the results show that higher overall economic growth can contribute to higher CO2 emissions. Contrarily, higher overall population growth and overall renewable energy consumption can help reduce CO2 emissions in the short run. Keywords: Panel ARDL, CO2 emissions, economic growth, renewable energy JEL Classifications: Q3, Q4, Q5 DOI: https://doi.org/10.32479/ijeep.9878